Test-retest reliability of lower limb muscle strength, jump and sprint performance tests in elite female team handball players - Fristrup, B.; Krustrup, P.; Kristensen, K. H.; Rasmussen, S.; Aagaard, P. (European Journal of Applied Physiology, 2024)
Purpose This study aimed to assess the reliability of lower limb muscle function (knee extensor/flexor peak torque, rate of torque development (RTD), impulse, and countermovement jump (CMJ) performance) and sprint performance (acceleration capacity).